Structure investigation of nanohybrid PDMA/silica hydrogels at rest and under uniaxial deformation1. Issue 29 (7th August 2015) - Rose, Séverine; Marcellan, Alba; Narita, Tetsuharu; Boué, François; Cousin, Fabrice; Hourdet, Dominique
<x xml:space="preserve">Abstract</x> Nano-hybrid hydrogels were prepared by cross-linking polymerization of N, N-dimethylacrylamide (DMA) within a dispersion of silica nano-particles.